2013
DOI: 10.1016/j.jhydrol.2012.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Land cover controls on summer discharge and runoff solution chemistry of semi-arid urban catchments

Abstract: cover controls on summer discharge and runoff solution chemistry of semi-arid urban catchments" (2013 Recharge of urban runoff to groundwater as a stormwater management practice has gained importance in semi-arid regions where water resources are scarce and urban centers are growing. Despite this trend, the importance of land cover in controlling semi-arid catchment runoff quantity and quality remains unclear. Here we address the question: How do land cover characteristics control the amount and quality of sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 100 publications
3
28
4
Order By: Relevance
“…3), possibly because road runoff is diverted into pervious soils, located at a greater distance from the stream network than at PB. These contrasts highlight the importance of variations in stormwater drainage system characteristics in controlling urban runoff quantity and quality rather than simply percentage urbanization, as found also to be the case in Tucson, Arizona (Gallo et al 2013).…”
Section: Heavy Metalsmentioning
confidence: 80%
See 1 more Smart Citation
“…3), possibly because road runoff is diverted into pervious soils, located at a greater distance from the stream network than at PB. These contrasts highlight the importance of variations in stormwater drainage system characteristics in controlling urban runoff quantity and quality rather than simply percentage urbanization, as found also to be the case in Tucson, Arizona (Gallo et al 2013).…”
Section: Heavy Metalsmentioning
confidence: 80%
“…Accumulated solutes are then available for mobilization during rainfall and subsequent runoff (Vidon et al 2009;Gallo et al 2013). The flushing process recorded in late summer led to higher NH 4 -N and Nk-N during the rising limb of the hydrographs in E, PB and Q (Fig.…”
Section: Temporal Dynamics In Water Quality Parametersmentioning
confidence: 99%
“…[], Chen and Driscoll [], Coats and Goldman [], Durdu and Cvetkovic [], Emmerson [], Fulweiler and Nixon [, ], Gallo et al . [, ], Goolsby et al . [], Granlund et al .…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Transport of N in streamflow is the second largest flux of N out of catchments (second to gaseous losses), can account for up to 20% of the change in catchment N storage [ Baker et al ., ; Mulholland et al ., ; Suddick et al ., ; van Breemen et al ., ], and can alter downstream biogeochemical cycling and ecosystem function [ Kaye et al ., ; Lohse et al ., ]. Land use, land cover, and climate can control N fluxes by altering catchment‐scale hydrologic responses [ Dougherty et al ., ; Gallo et al ., , ; Kaye et al ., ]; N cycling processes such as N mineralization, uptake, and denitrification [ Inwood et al ., ; Mulholland et al ., ]; by shifting the magnitude and direction of N exchange pathways such as N gas flux and atmospheric deposition [ Galloway et al ., ; Kaushal et al ., ; Lohse et al ., ], and by altering point and nonpoint anthropogenic N sourcing [ Stanley and Maxted , ; Tu , ].…”
Section: Introductionmentioning
confidence: 97%
“…However, modeling studies have suggested that the adaptability of LID designs to other regions is problematic, requiring modified solutions to be field tested in every location to confirm how they will perform (Gallo et al, 2012). Therefore, there is still a great need to evaluate these practices in the field and to collect quantitative data on LID practices performance, especially in the Southern part of the United States.…”
Section: Introductionmentioning
confidence: 99%